Coordinated decentralized reactive power optimization of multi-area power systems with discrete variables based on the alternating direction method of multipliers and Ward equivalence. (March 2019) - Shen, Zhijun; Liu, Mingbo; Lu, Wentian; Lin, Shunjiang
Highlights: Propose an equivalent power injection circuit for the transformer branch. Establish a decentralized RPO model based on Ward equivalence. Propose an ADMM-Ward algorithm and apply to the decentralized RPO problem. Results show the accuracy and the convergence performance of ADMM-Ward. Abstract: This paper proposes a coordinated decentralized reactive power optimization (RPO) approach for multi-area power systems with discrete variables. A decentralized RPO model is established, in which the sub-RPO model for each area is built respectively, while other areas taken as external networks are represented by Ward equivalent circuits, and also the load tap changing transformer branch is modeled as an equivalent power injection circuit in order to avoid repetitive updates of the equivalent admittance matrix. We add coupling constraints between areas, given as consensus constraints on the bus voltages at boundaries, which are favor to remain the equivalence between the decentralized RPO model and the original centralized RPO model. The model is then solved using the alternating direction method of multipliers (ADMM). The proposed approach requires very little exchange of boundary information among neighboring areas. Numerical results for IEEE test systems ranging in size from 9 to 118 buses with 2–4 areas and a real-world 739-bus system with 2–4 areas demonstrate that the proposed approach provides markedly improved convergence performance compared to the application of ADMM alone.